Improving the energy efficiency of induction machines by using combined windings machines - Makhsud K. Bobojanov; Furqat N. Tuychiev; Nuralibek Kh. Rashidov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Research in the field of electrical machines shows that energy efficiency is improved by higher material costs or by more expensive electrotechnical materials with improved properties. This, in turn, leads to an increase in the cost of the engine. Unlike the methods mentioned above, combined windings can be used to increase the energy efficiency of electrical machines without using additive technology or expensive electrotechnical materials. At the same time, improving the content of higher harmonics leads to a reduction in additional machine losses. Aim: Using a combined winding instead of a standard winding in an induction motor stator reduces additional losses in the stator winding and increases energy efficiency by reducing the proportion of higher harmonic components in the MMF distribution curve. Methods: To evaluate the advantages of the electromagnetic properties of the combined winding compared to the standard one, harmonic analyses were carried out and winding factor were calculated. Results: The amplitude of the harmonic components in the MMK for the combined winding has significantly improved compared to the standard winding. At the same time, the ratio of the main harmonic to the overall harmonic content improved by 3%, and the winding factor by approximately 3.5%. The general advantages of this type of special winding compared to standard winding are presented.